The Impact of Macroeconomic Fundamental Policies on The Composite Stock Price Index - Zhafa Nadhilla; Sriyono Sriyono (Agregat: Jurnal Ekonomi dan Bisnis, 2023)
This study aims to test the purpose of this study, namely to determine the effect of Gross Domestic Product, Inflation, Interest Rates and Rupiah Exchange Rate on the Composite Stock Price Index.This type of research uses quantitative methods and using secondary data. The data used in this study are time series of Gross Domestic Product, Inflation, Interest Rates, Rupiah Exchange Rate and JCI during the 2011-2020 period. Sampling from this study used the saturated sample method from the monthly data of each variable for 10 years, so that 120 samples were obtained. This research uses multiple linear analysis techniques with the application of eviews 9. The results of this study show that the Gross Domestic Product variable has a positive and significant influence on the JCI, the Inflation variable has a positive and significant influence on the JCI, the Interest Rate variable does not have a significant influence on the JCI and the Rupiah Exchange Rate variable has a negative and significant influence on the JCI.